Effectiveness of Using QR Code-Based Biotechnology Practical E-Instructions for Junior High School Students to Improve Critical Thinking Skills - Widyastuti Asy Syaffa; Iin Murtini (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2026)
The demands of 21st century education emphasize the importance of mastering critical thinking skills for students in order to be able to compete competitively. However, the reality in the field shows that the level of students' critical thinking skills is still in the low category. The causal factors are the use of media and teaching materials that are less interesting and less interactive. This study aims to determine the effectiveness of the biotechnology practical E-Instructions product through QR Code technology to improve students' critical thinking skills in junior high schools. The method used in this study was a field trial using the One Group Pre-test Post-test design on 32 ninth grade students of SMP Negeri 5 Tuban. Data collection was carried out through the T-Paired and N-Gain tests. The results showed a significant increase (Sig. 0.000) with an N-Gain of 0.74 (high criteria), proving that QR Code-based Practical E-Instructions are effective in improving students' critical thinking skills. This innovation is expected to be a solution in more interactive biotechnology learning and encourage students' critical analysis skills.